Mesoscale structure of the atmospheric boundary layer and its impact on regional air pollution: A case study. (1st August 2021) - Jin, Xipeng; Cai, Xuhui; Yu, Mingyuan; Wang, Xuesong; Song, Yu; Kang, Ling; Zhang, Hongsheng; Zhu, Tong
Abstract: The atmospheric boundary layer (ABL) is known for its vertical structure in affecting air pollution due to the dilution and ventilation capacity. But how this effect playing over horizontal scales is not well investigated. This study reveals the ABL structure over a sub-synoptic scale or mesoscale related to regional PM2.5 (particulate matter with an aerodynamic diameter less than 2.5 μm) pollution in the North China Plain (NCP). A typical PM2.5 pollution episode from December 1–4, 2017, is chosen for analysis, which is characterized by the rapid development of a vast polluted air mass along the mountainous side of the NCP extended hundreds of kilometers. In association with this episode, a shallow trough and a warm tongue at 850 hPa, with warm air advection in the upper layer and an orographic trough at the surface, provide favorable conditions for low-level warm front formation in the NCP. Surface meteorological data from 116 observatories and pollution-monitoring data recorded at 40 stations on the NCP are used to diagnose the hourly evolution of the meteorological and PM2.5 concentration fields, based on the California Meteorological (CALMET) model and a simple interpolation scheme. In addition to the surface wind, the equivalent potential temperature (EPT) is used to analyze air-mass boundaries or fronts at the surface. The results show that a block of colder air mass is gradually confined by warmer air, driven both from the southeast by a warm front and from the northwest by the thermal effect of the mountains. Consequently, a polluted air mass develops, with sharp boundaries indicated by both the discontinuity of wind fields and a strong gradient in the EPT. Numerical simulation using the Weather Research and Forecast model reproduces the meteorological evolution at the surface, revealing a three-dimensional ABL structure during this episode. With a dome-like warm cap covering the colder polluted air mass, an abrupt drop of ABL height occurs at the cross section from outside into this zone. Strong stratification suppresses the daytime ABL height to as low as 300 m over this zone. Thus, the cold air mass is confined not only laterally but also vertically. This ABL structure persisted throughout the daytime and night, in addition to weak winds in the nearly isolated air mass, which constitutes adverse dispersion conditions. This may help to explain the simultaneous increase in PM2.5 concentrations over a vast area of the NCP. Graphical abstract: Image 1 Highlights: The mesoscale ABL structure related to regional PM2.5 pollution in the North China Plain was revealed. The effect of synoptic and mesoscale processes on the ABL was analyzed. Warm front and mountain thermal effect formed a cold air pile with dome-like warm cap. PM2.5 pollution played as a tracer to display internal boundaries of the atmosphere.